Experimental observation of plasma wakefield growth driven by the seeded self-modulation of a proton bunch - Turner, M. (2019)
We measure the effects of transverse wakefields driven by a relativistic proton bunch in plasma with densities of 2.1×10^14 and 7.7×10^14 electrons/cm^3. We show that these wakefields periodically defocus the proton bunch itself, consistently with the development of the seeded self-modulation process. We show that the defocusing increases both along the bunch and along the plasma by using time resolved and time-integrated measurements of the proton bunch transverse distribution. We evaluate the transverse wakefield amplitudes and show that they exceed their seed value (<15 MV/m) and reach over 300 MV/m. All these results confirm the development of the seeded self-modulation process, a necessary condition for external injection of low energy and acceleration of electrons to multi-GeV energy levels.